PERAN END CHILD PORNOGRAPHY AND TRAFFICKING (ECPAT) DALAM MENGATASI TINDAKAN EKSPLOITASI KOMERSIAL PADA ANAK (ESKA) DI SEKTOR PARIWISATA THAILAND - Rahadian, Fathurrahman Adam; Pahlawan, Indra (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
Tourism is a major source of foreign revenue for Thailand, but its nightlife sector is often associated with the Commercial Sexual Exploitation of Children (CSEC), a form of human trafficking. With no single government agency directly addressing this issue, ECPAT has taken on the role of an independent actor to combat CSEC. Using qualitative research from 2018–2023, this study examines how ECPAT fills the state’s gap through policy advocacy, public awareness campaigns, and partnerships with government and private sectors via programs like Down to Zero, Disrupting Harm, and The TUI Academy. Despite its efforts, ECPAT faces challenges such as weak law enforcement, underreporting by victims, limited resources, and resistance from the tourism industry toward child protection initiatives. Keywords: ECPAT, CSEC, Sexual Exploitation, NGO